Environmental Study of Wilderness Aesthetic of Balochi Poetry Analysis of Homer Kilkori’s O Talo Taalo - Amin, Muhammad (Hanken, 2020)
This paper analyses Homer Kilkori’s romantic poetry O Tall and Nimble (O Talo Taalo او ٹلو ٹالو) on the ground of wilderness aesthetic. Particularly this topic refers an environmental study of wilderness. This paper suggests the way to get rid of environmental alienation, which comes from non-collective consciousness, and it entertains importance of wilderness aesthetic. The first premise of wilderness aesthetic I will draw from Berleant’s work and I will formalize his work to sketch a method. In this method language becomes essence / foundation of structure. For making the worth of concerning method I will utilize Porteous’ conception of ‘having’, ‘doing’ and ‘being’. These things present collective aesthetic consciousness. The paper will conclude that collective aesthetic consciousness provides a teleological ground which reserves collection against alienation.